Formation of Village Regulations in the Administration of Village Administration in Indonesia - Editya S, Maria Ferba; Saragih, Rayani; Firmantua, Edwardo (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
This article aims to determine the formation of village regulations in the implementation of village administration in Indonesia. The problem in this research is focused on the BPD process in preparing and establishing village regulations and the formation of village regulations in terms of the principles of forming good laws and regulations. To approach this problem, a theoretical reference to the statutory approach is used. Data was collected through literature study by examining laws and other references relevant to this research, then the data was analyzed qualitatively. This study concludes that the optimal role of the BPD is not sufficient in establishing village regulations together with the Village Head as an extension of the village community, this is because the village regulations that have been formed in the last 2 (two) years do not reflect community needs and community expectations. The position of village regulations is based on Law No. 23 of 2014 concerning Regional Government, Law No. 6 of 2014 concerning Villages, and Government Regulation No. 43 of 2014. . UU no. 10 of 2004 and Law no. 12 of 2011 view village regulations as legal products, and Law no. 32 of 2004 views village regulations as political products, not legal products. Meanwhile, Law No. 6 of 2014 sees village regulations on two sides, both as a legal product and as a political product.